2006
DOI: 10.1093/jac/dkl181
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of antimicrobial peptides as potential agents against several oral bacteria

Abstract: Our results support growing evidence suggesting the use of antimicrobial peptides for prevention and treatment of oral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 10 publications
4
84
1
1
Order By: Relevance
“…actinomycetemcomitans is resistant to LL-37. As previously observed (24), A. actinomycetemcomitans treated with LL-37 at physiological ionic strength maintained growth at all tested LL-37 concentrations (up to 100 g/ml) (Fig. 1A).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…actinomycetemcomitans is resistant to LL-37. As previously observed (24), A. actinomycetemcomitans treated with LL-37 at physiological ionic strength maintained growth at all tested LL-37 concentrations (up to 100 g/ml) (Fig. 1A).…”
Section: Resultssupporting
confidence: 87%
“…Surprisingly, although a lack of LL-37 was correlated with disease caused by A. actinomycetemcomitans overgrowth, this bacterium does not appear to be sensitive to LL-37 when tested in vitro (24). We therefore searched for additional mechanisms by which LL-37 might control the growth of A. actinomycetemcomitans in the oral cavity.…”
mentioning
confidence: 99%
“…The general mechanisms of microbial resistance to AMPs, which are valid both for the planktonic and sessile states, include mutations that affect the structure and charge distribution of the cytoplasmatic membrane, modifications to the lipopolysaccharide structure of Gram-negative bacteria, and active pumping of the AMPs out of the cell (Altman et al 2006). Specifically, it has been reported that Gram-negative bacteria have evolved mechanisms to remodel the composition of the outer membrane through modification of the LPS molecules (Miller et al 2005), which impairs LPS-binding AMPs.…”
Section: Biofilm Resistance To Antimicrobial Peptidesmentioning
confidence: 99%
“…Porphyromonas gingivalis is an oral anaerobe and the pathogen most associated with chronic periodontal disease (16,18,42). P. gingivalis has previously been found to be highly resistant to antimicrobial peptides (1,33). The Arg-gingipains and Lys-gingipain cysteine proteases (cleaving after arginine and lysine, respectively) are among the major virulence factors expressed and secreted by P. gingivalis.…”
mentioning
confidence: 99%